Limited dilute lidocaine anesthesia: A useful technique with many practical applications. (21st February 2022) - Green, Jeremy B.; Layt, Craig
Abstract: Background: Limited dilute lidocaine infiltration facilitates a comfortable procedure and a rapid recovery process following a novel intervention for reduction of cellulite. Infiltration of dilute lidocaine has many other practical applications in dermatologic surgery. Objectives: This article describes a safe, effective technique for local infiltration of limited volume dilute lidocaine anesthesia in a cellulite reduction procedure. Methods: The limited dilute lidocaine technique was utilized in studies of a novel device designed to reduce the appearance of cellulite by focal release of fibrous septa in a minimally invasive procedure. No sedation was used. A small (27‐ to 30‐gauge) needle was used to deliver anesthesia to the entry sites. Then, a 20‐gauge spinal needle was tunneled under the skin in the superficial plane to manually deliver anesthetic along the advancement pathway of the device and marked cellulite targets. Results: During the initial studies, the mean delivered anesthesia volume was 357.2 ml (range, 250–525 ml) or 18.7 mg/kg (range, 11.1–28.4 mg/kg). The mean anesthesia time was 16 min (range, 8–32 min). The mean number of cellulite depressions treated was 19.8 (range, 11–34). Adverse events were closely monitored, and there were no signs of toxicity in any study patients. There were very low levels of discomfort; all patients reported the procedure was tolerable. This technique facilitates a time‐efficient procedure and minimizes weeping of excess fluid during recovery. Conclusions: When administered with care and skill, the limited dilute anesthesia technique is a safe, effective approach for local anesthesia with many practical applications in dermatologic surgery.